Cytotoxic effect of Shiga toxin-2 holotoxin and its B subunit on human renal tubular epithelial cells - Pistone Creydt, Virginia (2006)
Shiga toxin-producing Escherichia coli produces watery diarrhea, hemorrhagic colitis and hemolytic-uremic syndrome (HUS). In Argentina, HUS is the most common cause of acute renal failure in children. The purpose of the present study was to examine the cytotoxicity of Stx type 2 (Stx2 holotoxin) and its B subunit (Stx2 B subunit) on human renal tubular epithelial cells (HRTEC), in the presence and absence of inflammatory factors. Cell morphology, cell viability, protein synthesis and apoptosis were measured. HRTEC are sensitive to both Stx2 holotoxin and Stx2 B subunit in a dose- and time-dependent manner. IL-1, LPS and butyrate but not TNF, IL-6 and IL-8, increased the Stx mediated cytotoxicity. The effects of Stx2 B subunit appear at doses higher than those used for Stx2 holotoxin. Although the physiological importance of these effects is not clear, it is important to be aware of any potentially toxic activity in the B subunit, given that it has been proposed for use in a vaccine.